Effects of dexmedetomidine on perioperative monitoring parameters and recovery in patients undergoing laparoscopic cholecystectomy in a 300 bedded hospital, Jaipur - Mohit Kumar; Varun Kumar Saini; Kumar Asnani; Vivek Singhal; Rajesh Bhargava; Shaveta Kataria (Creative Pharma Assent, 2022)
Background: Laparoscopic cholecystectomy has emerged over the open cholecystectomy as gold standard for surgical treatment of symptomatic gall stones. Although pain after laparoscopic cholecystectomy is less intense, but many patients may experience considerable pain during first 24 hours in post-operative period. Intravenous (i.v.) use of dexmedetomidine in perioperative period lead to 90% decrease in the serum catecholamine levels, and further diminishing the haemodynamic response and sedating the patient and decrease analgesic requirements in the post-operative period. The efficacy of dexmedetomidine in providing hemodynamic stability during perioperative period and anesthesial recovery in patients undergoing laparoscopic cholecystectomy is studied. Methods: 60 patients of ASA grade I and II and of either sex (20–50 years) allocated in one of two parallel groups containing 30 patients each. In Group A- Dexmedetomidine (i.v.) bolus over 10min and continuous maintenance infusion 0.5µg/kg/h and in group B-0.9% normal saline i.v. bolus and continuous maintenance infusion was done. Parameters noted were heart rate, mean arterial pressure, oxygen saturation, post-operative pain were evaluated using VAS and analgesic requirement. Results: Both the groups were similar results in terms of age, sex, weight, ASA status, duration of surgery and hemodynamic parameters. SBP, DBP, MAP, SpCO2, EtCO2 values for both the groups were similar at all the intervals of time. No significant side effects were noted. Conclusion: Dexmedetomidine, pre-anaesthetic medication and its intraoperative infusion, further reducing the intraoperative anaesthetic requirement, sympathoadrenal response to intubation, maintains intraoperative cardiovascular stability, smooth extubation, sedation, and reduction in postoperative complications.